Critical factors in willingness to participate in forest management: tiie case of Gamiiari Forest Reserve, Oyo state, Nigeria. (2003)
The study investigated the factors that could motivate members of forest adjoining communities to participate in the management of Onigambari Forest Reserve, Oyo State, Nigeria. Stratified quota sampling was used to select one hundred and fifty- eight respondents among the local community members. Data processing was by simple statistics, chi-square test of independence and logistic regression analysis. Results indicate that application of financial incentives does not have significant, effect on willingness to participate (p > 0.05), but the effects of non-financial), incentives and sociological factors are significant (p < 0.05). Results of logistic regression show that age, educational Status; incentive requirement (technical) and roles played in forest management have significant impact on willingness to participate in forest management will a log likelihood ratio of 278.317 (X(2) tab.= 124.342: df.= l38 and P= 0.05) . In view of the fact that socio-economic factors such as age; education; incentive requirement. tennurial rights, marketability of forest products and forest protection technics have significant effect on willingness to participate; it is recommended that government should embark on massive awareness campaign to educate the people on the benefits they stand to derive by actively participating in forest management. The practice of latmgya should be encouraged in order to motivate landless strangers to participate in forest regeneration. The forest reserve should be managed to supply multiplicity of goods and Services for: Social acceptability and ecological sustainability. Community Associations should be encouraged to establish nurseries from which timber takers would be required to purchase seedlings for replacing felled trees.